2012
DOI: 10.1007/s00404-012-2638-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of laparoscopic bipolar electrocoagulation and intracorporeal suture application to ovarian reserve in benign ovarian cysts

Abstract: The unwanted effect of bipolar electrocoagulation on ovarian reserve is probably transient and causes minimal damage to ovary. FSH levels may be slightly elevated. Gentle use of bipolar electrocoagulation or intracorporeal are not found to effect ovarian reserve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The heterogeneity of benign cysts among certain studies could also subject their results to potential bias. 18,19,21 Selection bias could also apply in the case of retrospective studies. 17,23 Finally, only 2 studies reported that they were statistically adequately powered.…”
Section: Weaknesses Of the Studymentioning
confidence: 98%
See 1 more Smart Citation
“…The heterogeneity of benign cysts among certain studies could also subject their results to potential bias. 18,19,21 Selection bias could also apply in the case of retrospective studies. 17,23 Finally, only 2 studies reported that they were statistically adequately powered.…”
Section: Weaknesses Of the Studymentioning
confidence: 98%
“…15,16 Included studies Eight studies were finally included in our systematic review, which recruited 545 women. [17][18][19][20][21][22][23][24] Among them, 266 women (48.8%) were treated with bipolar electrocoagulation after the excision of the ovarian cyst, whereas the remaining 279 (51.2%) were treated with hemostatic suturing. In Table 1, we present the methodological characteristics of these studies.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Of the 18 citations evaluated in full-text, 2 were case reports (17,20), 2 did not report effect of haemostatic method on ovarian reserve (21, 22), 3 did not report preoperative AMH values and therefore did not allow calculation of change after surgery (23)(24)(25), and 2 overlapped with more recent publications that were included in this analysis (26,27), 1 reported on non-endometriotic cysts (28), 1 did not report AMH levels at all (16), and 1 compared laparoscopic cystectomy and BD with laparotomy and suturing (29), and thus were excluded. A total of 6 studies were included in the systematic review; four of these six studies (3 randomized controlled trials (RCT), 1 prospective cohort study) were deemed eligible for inclusion in the meta-analysis.…”
Section: Literature Search and Study Selectionmentioning
confidence: 98%
“…Residual ovarian tissue bleeding can be addressed by suturing or bipolar electrocautery without long-term decrease in ovarian function. 13 …”
Section: Simple Cystsmentioning
confidence: 97%